Avaliação da composição genética de linhagens de tilápia do Nilo (Oreochromis niloticus) e das gerações G0 e F1 da linhagem GIFT - Lupchinski Júnior, Enio (2007)
In tropical fishes, the GIFT strain development of O. niloticus called attention by the world's genetic improvement history. In Brazil, the "Estação Experimental de Piscicultura da Universidade Estadual de Maringá" (UEM - CODAPAR) received the first specimens of GIFT strain, in March 2005. The objective of the first study was to estimate, through the RAPD technique, the genetic structure of three commercial Nile tilapia strains (Bouaké, Chitralada and GIFT). The genetic divergence values were 0.262 to Bouaké, 0.366 to Chitralada and 0.318 to GIFT strain. The Gst and Nm values were 0.081 and 5.708, 0.106 and 4.238, and, 0.070 and 6.656, for Bouaké related to Chitralada, Bouaké to GIFT, and Chitralada to GIFT strain, respectively. The index of Shannon values were 0.473 to Bouaké strain, 0.544 to Chitralada, and 0.469 to GIFT. The results indicated that the strains did not lose genetic variability or divergence in a significant way. The data group also indicated that there were no significant genetic alterations in any of the three Nile tilapia strains. The aim of the second research study was to analyze, through the RAPD technique, the genetic variability and divergence from the two first GIFT generations raised in Brazil (G0 and F1). The polymorphic loci percentages were 69.6% to the G0 generation and 60.0% to the F1 generation. The Shannon index values were 0.367 to the breeders (G0) and 0.317 to the offspring (F1). The values of genetic divergence were 0.213 to G0, and 0.208 to F1. The results demonstrated that there was a genetic variability loss from G0 to F1 generation. Also, indicated a high genetic variability in both G0 and F1 generations. The data group indicated, in addiction, that the genetic diversity was kept during the GIFT strain establishment. The RAPD technique was a useful tool to the genetic structure analysis of Bouaké, Chitralada and GIFT strains; as well as to the two raised GIFT Nile tilapia generations.